An Unusual Case of Cheiralgia Paresthetica Caused by Lipoma - Mačiulaitis, Tomas; Jucaityte, Aira; Minderis, Mindaugas (Lietuvos chirurgija, 2024)
Cheiralgia paresthetica (CP) is a distinctive clinical condition arising from the compression of the superficial branch of the radial nerve (SBR). Typically, CP manifests as a burning-type pain in the dorsal and radial aspect of the hand. Existing literature highlight various etiological factors contributing to this condition, including constriction of the wrist, as with tight wristwatches or handcuffs. Symptoms may also arise from blunt traumas, distal radius fractures, and iatrogenic causes. However, CP induced by a lipoma is an exceptionally rare phenomenon. In this context, we present a case exemplifying the diagnosis and management of lipoma-induced CP.